Effect of PHET-assisted Wondering, Exploring, and Explaining Model on Students’ Cognitive Outcomes in Global Warming - Rusmiati, Siti; Aripin, Aripin; Makiyah, Yanti Sofi (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2025)
A preliminary study at SMA Negeri 9 Tasikmalaya revealed that students’ low activity and engagement during the learning process contributed to poor learning outcomes. This was evident from the average score of students’ daily tests, which was 62, below the Minimum Mastery Criteria (MMC) of 75, thus categorized as low. This study aims to examine the effect of the Wondering, Exploring, Explaining (WEE) learning model assisted by PhET on students’ cognitive learning outcomes in the topic of global warming among tenth-grade students at SMA Negeri 9 Tasikmalaya in the 2023/2024 academic year. The study employed a quasi-experimental method with a non-equivalent control group design across nine tenth-grade classes. The sample was determined through purposive sampling, with class X-3 assigned as the experimental group and class X-9 as the control group. Cognitive learning outcomes were measured using an essay test consisting of nine items covering cognitive levels C2, C3, and C4. Hypothesis testing using the t-test at a significance level (α=0.05) showed that , namely 11,5 > 1,67, indicating that  was accepted and is rejected. It can thus be concluded that the WEE learning model assisted by PhET significantly influenced students’ cognitive learning outcomes on the topic of global warming. The findings of this study imply that the WEE learning model assisted by PhET can serve as an effective instructional strategy for teachers to enhance student engagement and learning outcomes and may provide a reference for further research in the development of innovative learning models.